Coulometry on the voltammetric timescale: Microdisk potential-step chronoamperometry in aprotic solvents reliably measures the number of electrons transferred in an electrode process simultaneously with the diffusion coefficients of the electroactive species - Paddon, C; Silvester, D; Bhatti, F; Donohoe, T; Compton, R (2007)
Microdisk, single potential-step chronoamperometry, is applied to a range of organic substrates in the aprotic solvents tetrahydrofuran, propylene carbonate, acetonitrile and the room temperature ionic liquid [C 4dmim][N(Tf)2]. Fitting of the chronoamperometric transients was achieved using the Shoup and Szabo method [3]. Accurate values for the diffusion coefficients, D, and the number of electron(s) transferred, n, in the electrode process have been simultaneously and consistently obtained. This method is shown to be generally applicable and reliable for the determination of the number of electrons transferred in faradaic processes uncomplicated by relatively slow coupled homogeneous kinetics. Since the experiment is conducted essentially on typical voltammetric timescales it can be commended as a complementary technique for classical coulometry which is only possible on much longer timescales. The chronoamperometric method is therefore likely to be of greater relevance to the interpretation of voltammetric data. © 2007 Wiley-VCH Verlag GmbH and Co. KGaA.